2017
DOI: 10.15294/biosaintifika.v9i1.9210
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Heading Date Six (Hd6) Gene Derived from Rice Mutant Varieties

Abstract: Genes which were associated with flowering time to indicate the early maturity is known as heading date (Hd). Heading date six (Hd6) gene was identified from rice mutant varieties were Atomita 2, Atomita 3, Atomita 4, Bestari, Cilosari, Diah Suci, Sidenuk, Kahayan, Mayang, Meraoke, Mira-1, Pandan Putri, Superwin, Suluttan Unsrat 1, Suluttan Unsrat 2, Winongo, Woyla, Yuwono, while the rice var. Nipponbare was used as a positive control. All of rice mutant varieties derived from mutation induction by the dose of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…Mira-1 rice variety as a wild rice was moderately susceptible ( MS ) to neck blast disease. The previous study [22] found that rice mutant lines carry resistance to Xa5 bacterial leaf blast disease. Furthermore, Dwipa et.al [23] also reported from 17 brown and black rice tested, they found 7 genotypes were resistant and another 2 genotypes were moderately resistant to blast disease.…”
Section: Resultsmentioning
confidence: 98%
“…Mira-1 rice variety as a wild rice was moderately susceptible ( MS ) to neck blast disease. The previous study [22] found that rice mutant lines carry resistance to Xa5 bacterial leaf blast disease. Furthermore, Dwipa et.al [23] also reported from 17 brown and black rice tested, they found 7 genotypes were resistant and another 2 genotypes were moderately resistant to blast disease.…”
Section: Resultsmentioning
confidence: 98%
“…People could directly access and more easily observable traits could be created (Cieslak et al, 2017). According to International Atomic Energy Agency (IAEA), more than 400 rice varieties being developed worldwide (Li et al, 2016) and NNEA/BATAN has released 21 of new rice varieties from this technique (Aryanti et al, 2017). Gamma rays produces Reactive Oxygen Species (ROS), which interact with DNA and cause oxidative damage such as base modifications and single/double strand breaks (Arjona and Ariza, 2009;Morita et al, 2009).…”
Section: Introductionmentioning
confidence: 99%